Construction of a two-photon fluorescent probe for ratiometric imaging of hypochlorous acid in alcohol-induced liver injury. Issue 86 (8th October 2019) - Lou, Yan; Wang, Caixia; Chi, Siyu; Li, Songjiao; Mao, Zhiqiang; Liu, Zhihong
Abstract : A ratiometric two-photon fluorescent probe for HClO was deliberately constructed to reveal the generation of HClO in alcohol-induced liver injury. Abstract : Alcohol-induced liver injury has been a terrible threat to human health and life. The relationship between HClO and the process is unclear. Thus, a ratiometric two-photon fluorescent probe for HClO was deliberately constructed and revealed the generation of HClO in the alcohol-induced liver injury process for the first time.